Oligocene crabs (Decapoda: Brachyura) from the Asmari Formation in Yasuj area (SW Iran) - Bahrami, Ali; Ossó, Àlex; Yazdi, Mehdi; Ansari, Heshmatollah (Acta Geologica Polonica, 2023)
New findings of crustacean decapod brachyurans from the Rupelian period (lower Oligocene) in Iran are presented in this study. In particular, Lophoranina sp. and Palaeocarpilius cf. P. rugifer Stoliczka, 1871, from the Rupelian strata were found in two previously unexplored localities, Abshar and Vezg near Yasuj in the southwestern region of Iran. The discovery contributes to fill the gap in the record of brachyuran decapod crustaceans in Iran during the Eocene and Miocene periods. The presence of both genera in the Oligocene of Iran suggests a certain degree of faunal similarity among brachyurans on both sides of the Tethys Realm.
Keywords: Paleogene; Rupelian; Tethys; Brachyura; Palaeocarpilius; Lophoranina